Exogenous Ca2+ mitigates the toxic effects of TiO2 nanoparticles on phagocytosis, cell viability, and apoptosis in haemocytes of a marine bivalve mollusk, Tegillarca granosa. (September 2019) - Guan, Xiaofan; Tang, Yu; Zha, Shanjie; Han, Yu; Shi, Wei; Ren, Peng; Yan, Maocang; Pan, Qicun; Hu, Yuan; Fang, Jun; Zhang, Jiongming; Liu, Guangxu
Abstract: Phagocytosis suppression induced by nanoparticles (NPs) exposure is increasingly reported in marine species. However, the mechanisms underlying this impact remain poorly understood. In order to improve our present understanding of the immunotoxicity of NPs, acute (96 h) TiO2 NP exposure and rescue trials via exogenous supply of Ca 2+ were performed in the blood clam, Tegillarca granosa . The results show that the phagocytosis rate, cell viability, and intracellular Ca 2+ concentration of haemocytes were significantly suppressed, whereas the intracellular ROS concentration of haemocytes significantly increased upon nTiO2 exposure. Exposure to nTiO2 also led to the significant downregulation of Caspase-3, Caspase-6, apoptosis regulator Bcl-2, Bcl-2-associated X, calmodulin kinase II, and calmodulin kinase kinase II. Furthermore, the toxic impacts of nTiO2 were partially mitigated by the addition of exogenous Ca 2+, as indicated by the recovery tendency in almost all the measured parameters. The present study indicates that Ca 2+ signaling could be one of the key pathways through which nTiO2 attacks phagocytosis. Graphical abstract: Image 1051475 Highlights: nTiO2 suppressed phagocytosis, cell viability, and Ca 2+ content of haemocytes. The ROS concentration in haemocytes was induced by nTiO2 exposure. nTiO2 downregulated the expression of apoptosis and Ca 2+ signaling related genes. The toxic impacts of nTiO2 were partially mitigated by adding exogenous Ca 2+ Abstract : The toxic effects of nTiO2 on phagocytosis, cell viability, and apoptosis of Tegillarca granosa and the rescue effects of exogenous Ca 2+ were demonstrated.